Fungal inoculation effect on post-harvest sugarcane residue decomposition under field conditions - Maza, Marianela (2018)
Fungal inoculation effect on post-harvest sugarcane residue (SCR) decomposition in field conditions was studied. In vitro interaction between selected fungi was determined by direct confrontation. Mycelial growth response to different concentrations of herbicides and urea was also assessed. Fungal combinations did not show inhibitory effects. Bjerkandera sp. Y-HHM2 and Myrothecium sp. S-3.20 growth decreased in 2.4-D agar plates. However, Pleurotus sp. Y- RN3 showed a stimulation in 10 ppm 2.4-D agar plates. The biggest growth in ametrine supplemented cultures was observed in Pleurotus sp. Y-RN3. Evaluation of increasing urea concentrations on mycelial growth showed that 5,000 ppm significantly inhibits mycelial growth. The field assay under rainfed condition showed that post-harvest SCR decomposition rate significantly increases in Y-HHM2, Y-RN3 and Y-HHM2/Y-RN3/S-3.20 treatments. This is the first report on the capability of Bjerkandera sp. Y-HHM2 and Pleurotus sp. Y-RN3 to accelerate post-harvest SCR decomposition in rainfed conditions at field scale, suggesting that these fungi might be useful tools in the sugarcane crop system.